Comparison of BIM and Conventional Method to Analyze Dimension and Volume of Abutment - Rayhan Anugrah Yuliano; Nunung Martina; Safri # (POLITEKNIK NEGERI JAKARTA, 2022)
The development of the industrial era 4.0 is rapid, one of which is the BIM (Building Information Modeling) method for surveying activities, namely 3D Scanning. The 3D Scanning method, which can obtain millions of points in point clouds in one scan, is expected to provide higher accuracy and more efficient and effective operating time than conventional methods. Conventional methods, which still apply human plotting, require more time and human resources because they have to move from one point to another, and their accuracy is highly dependent on the quality of human resources. This research was conducted at the Interchange Project of the Batang Industrial Estate, Central Java, and aimed to compare the dimensions, volume, and shop drawings of the 3D Scanning method with the conventional method and the advantages of the 3D Scanning and Modeling method. The results obtained in this study are that there is an average dimension difference of 0.007 m from the shop drawing image, then there is a difference in the average coordinate point of 0.028 m which causes the Abutment position to shift from the shop drawing image. BIM is one method for get the volume of structures on Interchange Project with careful results and faster process. The calculated volume is based on shop drawings. The results showed that the difference between the conventional BIM method in the volume of concrete was 1.156%, and in the granular heap, there was a difference of 1.292%. The advantages of these 2 BIM methods are how they operate, which has started to implement an automation system and requires less time than conventional methods.